A new methodology for assisting quality control of NSM-CFRP systems since very early ages - Fernandes, Pedro Miguel Gomes (2014)
The performance of NSM systems directly depends on the performance of the adhesive which can only be reached if a proper curing conditions and time are assured. In order to assess the curing process of the adhesives, as well as the corresponding bond behavior, adequate non-destructive testing approaches are required. Nonetheless, scarce information could be found in the literature in concern to this relevant topic. To fill such gap, the present paper proposes a new method for continuous quality control of epoxy adhesives, based on adaptations of an existing technique originally devised for continuous monitoring of concrete E-modulus since casting, called EMM-ARM (Elasticity Modulus Monitoring through Ambient Response Method). This work reports the simultaneous study of the adhesive through EMM-ARM, together with direct pullout tests at several ages on concrete specimens strengthened with NSM CFRP laminate strips using the same epoxy. The tests are described, and the obtained results are presented and discussed, highlighting the potential of applying EMM-ARM for quality control and decision-making assistance of NSM systems.